2019
DOI: 10.1007/s00394-019-02068-4
|View full text |Cite
|
Sign up to set email alerts
|

Does l-carnitine supplementation affect serum levels of enzymes mainly produced by liver? A systematic review and meta-analysis of randomized controlled clinical trials

Abstract: Abargouei, A 2020, 'Does L-carnitine supplementation affect serum levels of enzymes mainly produced by liver? A systematic review and meta-analysis of randomized controlled clinical trials',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 95 publications
3
15
0
Order By: Relevance
“…Nevertheless, the lack of significant differences in both, SOD and triglycerides between groups points toward different reasons behind the reduced numerical values of AST in the CARN group. Accordingly, elevated AST levels are not specific to liver disease, but are also related to skeletal muscle metabolism and cardiomyopathy ( Pirmadah et al, 2020 ). At this point, it must be remembered that early feed restricted lambs showed increased catabolism of proteins and hypertrophic cardiomyopathy caused by mitochondrial dysfunction ( Santos et al, 2018b ), so dietary L-Carnitine might have exerted some protective effects in the present study; the reduced heart weight in the CARN group together with reduced numerical levels of CK, a marker of muscle metabolism and damage ( Yarizadh et al, 2020 ), would be aligned with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the lack of significant differences in both, SOD and triglycerides between groups points toward different reasons behind the reduced numerical values of AST in the CARN group. Accordingly, elevated AST levels are not specific to liver disease, but are also related to skeletal muscle metabolism and cardiomyopathy ( Pirmadah et al, 2020 ). At this point, it must be remembered that early feed restricted lambs showed increased catabolism of proteins and hypertrophic cardiomyopathy caused by mitochondrial dysfunction ( Santos et al, 2018b ), so dietary L-Carnitine might have exerted some protective effects in the present study; the reduced heart weight in the CARN group together with reduced numerical levels of CK, a marker of muscle metabolism and damage ( Yarizadh et al, 2020 ), would be aligned with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses showed that L-carnitine supplementation improved steatosis and NASH ( 67 ) and carnitine supplementation in NAFLD patients could reduce AST, ALT, TG, and HOMA-IR ( 95 ). In yet another meta-analysis, L-carnitine supplementation was found to significantly improve the circulating levels of ALT, AST, and gamma-glutamyl transpeptidase (γ-GT), which may have a positive impact on liver function ( 96 ).…”
Section: Treatment Of Nafld With L-carnitine Supplementationmentioning
confidence: 99%
“…The recommended dose of L-carnitine is 15 g/day for healthy individuals ( 123 ) and 100–400 mg/kg/day for patients with carnitine deficiency ( 96 ). Some side effects have been observed after high-dose supplementation of L-carnitine, such as diarrhea, intestinal problems, and trimethylamine production that causes a fishy odor.…”
Section: Treatment Of Nafld With L-carnitine Supplementationmentioning
confidence: 99%
“…These enzymes are secreted by the liver, heart cells, and other organs, namely the pancreas, muscle tissue, and kidneys; however, the liver is the main organ that produces AST and ALT (Kim et al, 2005; Purcell, Behenna, & Walsh, 1979). These enzymes play a pivotal role in gluconeogenesis and amino acid metabolism (Dufour et al, 2000; Pirmadah et al, 2020). Although serum levels of ALT and AST can be used to diagnose liver disease, they are less specific markers for this condition, as high AST levels, in particular, are seen following skeletal muscle, brain, heart, and red blood cells damage (Pirmadah et al, 2020; Pratt & Kaplan, 2000).…”
Section: Introductionmentioning
confidence: 99%